2013
DOI: 10.1245/s10434-013-3183-3
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer Associated with Multiple Primary Cancers: Surgical Approaches and Long-term Survival

Abstract: A range of surgical approaches for esophageal cancer is available in patients associated with MPCs. However, curative resections for primary esophageal cancer associated with MPCs are feasible in highly selected patients. Therefore, a multidisciplinary team management approach is essential for customized treatment strategies in patients with esophageal cancer associated with MPCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 16 publications
3
48
0
Order By: Relevance
“…Regarding associated neoplasms, meanwhile SCC is known to be frequently associated with oropharingeal tumors (probably because of field cancerization), it seems that EA is associated with gastric adenocarcinoma -the incidence of gastric adenocarcinoma in patients with EA was 500:10 000 and in the general Brazilian population it is about 1:10 000. This finding is also in accordance with literature (4,10) . In this study, familial history of esophageal cancer did not correlate to increased risk of EC.…”
Section: Discussionsupporting
confidence: 94%
“…Regarding associated neoplasms, meanwhile SCC is known to be frequently associated with oropharingeal tumors (probably because of field cancerization), it seems that EA is associated with gastric adenocarcinoma -the incidence of gastric adenocarcinoma in patients with EA was 500:10 000 and in the general Brazilian population it is about 1:10 000. This finding is also in accordance with literature (4,10) . In this study, familial history of esophageal cancer did not correlate to increased risk of EC.…”
Section: Discussionsupporting
confidence: 94%
“…Some authors figured out, even if the rate of radical resection of esophageal lesion was comparable, the presence of additional head and neck tumors was associated with a worse long-term prognosis 8. According to Lee et al, when half of the resections were radical, 5-year survival was only 9.2% in patients receiving surgery for esophageal and head-and-neck cancer 9. However, Otowa, Y. et al addressed no differences in OS in patients with or without MPC receiving surgery in a non-randomized controlled study, but the extraordinarily high 5-year survival indicated possible strict selection of participants 10.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reported poor survival outcomes for these patients: 3- and 5-year survival rates were 25.0% and 10.6%, respectively. A recent study proposed surgical treatment should be considered for select EC patients with synchronous SPC [ 22 ]. The rate of curative resections for both EC and SPC was 87.5% in patients with gastric cancer, 52.9% in lung cancer and 47.1% in head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%